Determination of PtAuPd metal sequences for electrodeposition on graphene oxide for anode catalyst improvement in methanol oxidation - Suwapid Themsirimongkon (2018)
© 2017 Taylor & Francis Group, LLC. The orders of metal deposition (e.g. Pt, Au and Pd) on graphene oxide (GO) and their electrocatalytic properties were investigated. The mono-, bi- and tri-metallic nanoparticles were electrochemically prepared for catalyst preparation. The electrocatalytic activities of the catalysts in 0.5 M CH 3 OH + 0.5 M H 2 SO 4 solutions were examined. The results showed that the tri-metallic catalysts had higher catalytic activity and stability than the other catalysts. The results indicated that the existing Au and Pd layers before loading of Pt could improve the catalytic activities towards the methanol oxidation.